Five Reasons for the Failure to Diagnose Aldosterone Excess in Hypertension - Piaditis, George P.; Kaltsas, Gregory; Markou, Athina; Chrousos, George P. (Hormone and Metabolic Research, 2020)
Primary hyperaldosteronism (PA) is a well-known cause of hypertension although its exact prevalence amongst patients with apparent essential hypertension has been a matter of debate. A number of recent studies have suggested that mild forms of PA may be relatively common taking into consideration factors that were previously either overestimated or ignored when developing diagnostic tests of PA and when applying these tests into normotensive individuals. The performance characteristics and diagnostic accuracy of such tests are substantially increased when the adrenocorticotrophin effect, inappropriate potassium levels and their application in carefully selected normotensive individuals are considered. In the present review, we critically analyze these issues and provide evidence that several, particularly mild, forms of PA can be effectively identified exhibiting potentially important clinical implications.
Keywords: primary aldosteronism; hypertension; ACTH - adrenal; aldosterone to renin ratio